A collusion-resistant public auditing scheme for shared cloud data. (10th May 2019) - Nan, Fulin; Tian, Hui; Wang, Tian; Cai, Yiqiao; Chen, Yonghong
With the increasing popularity of collaboration in the cloud, shared data have become a new branch of cloud data, which also brings new challenges for remote integrity auditing. To address the concerns, this paper presents a novel public auditing scheme for shared data. Differing from the existing works, we introduce a new entity called local authentication server to finalise the block tags of shared data, which can thereby prevent the collusion attack effectively. Moreover, thanks to the new mechanism of tag generation, our scheme relieves the user manager of the burden of management and largely reduces the computation and communication overheads. In addition, we extend the scheme to support batch auditing by employing the aggregate BLS signature technique. The theoretical proof and experimental evaluation demonstrate that the proposed scheme can provide excellent security and outperform the previous ones in computational costs in the user revocation phase.